Students' Responds of Learning Vocabularies by Watching Youtube of The Computer Science Students of Cokroaminoto Palopo University - Tsamratulaeni (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2022)
This research focused on students’ respons of learning vocabulary by watching youtube. This research aimed to know the students’ respons of learning vocabulary by watching youtube. This research used a descriptive quantitative method. The subject of this research was the students of fourth semester of technical information. This study involved thirty two students as the research participants to respond to questionnaire. The data of students’ respons was obtained from the result of the questionnaire. From the data that obtained, the students have positive respons by watching youtube in learning English especially vocabulary. Most of the students agreed that they like youtube because it helped them learn English. Another positive effect was that the students’ vocabulary improved. Hence, the findings suggest that youtube can be used as the alternative teaching media to improve students’ learning English especially learning vocabulary.